Peran Pemerintah Dalam Menanggulangi Kerusakan Infrastruktur Jalan Di Kabupaten Bone - Nilawati, Nilawati; Mahsyar, Abdul; Tahir, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to describe the role of government in overcoming damage to road infrastructure in Bone regency. The method of this study used descriptive qualitative. The number of informan were 4 people. The result of this study showed that the role of government had performed its duties and responsibilities as an organizer policy. And in the provision of government facilities, it needed to review location so that the government knew the needs.. but in a large project or development.. it was hard for the ragional government or related agencies to give authority to their work partners then the work partner who would be responsible for the provision of facilities. The ragional government or related agencies continued to carry out their supervision and could not be separated responsible. Keywords: Government Role, Road Infrastructure Damage